Comparative evaluation of four SARS-CoV-2 antigen tests in hospitalized patients. (April 2021) - Thommes, Lis; Burkert, Francesco Robert; Öttl, Karla-Wanda; Goldin, David; Loacker, Lorin; Lanser, Lukas; Griesmacher, Andrea; Theurl, Igor; Weiss, Günter; Bellmann-Weiler, Rosa
Highlights: SARS-CoV-2 antigen tests allow rapid identification of symptomatic subjects. Out of four antigen tests, one showed insufficient sensitivity in COVID-19 patients. Antigen tests can stay positive after patients are no longer considered contagious. Abstract: Objectives: Rapid identification of infected subjects is a cornerstone for controlling a pandemic like the current one with the SARS-CoV-2. Easy to handle antigen tests can provide timely results, which is of particular importance in a primary care setting. However, concerns exist regarding their sensitivity, which led us to evaluate four commercially available tests in patients hospitalized for COVID-19. Methods: We analyzed in parallel nasopharyngeal/oropharyngeal swabs from 154 consecutive patients admitted to our department with moderate to severe COVID-19, using quantitative RT-PCR (Cobas, Roche) and up to four antigen tests from different distributors. Antigen test results were linked to Ct (cycle threshold) values as markers for patients' infectivity. Results: We found that two out of four antigen tests correctly identified subjects with high viral loads (Ct ≤ 25), and three out of four tests detected more than 80% of subjects with a Ct ≤ 30, which is considered the threshold for infectivity. However, one test investigated had a poor clinical performance. When investigating subjects with Ct values >30, we found that the antigen test was still positive in up to 45% of those cases. Conclusion: Most antigen tests had a sufficient sensitivity to identify symptomatic subjects infected with SARS-CoV-2 and with transmissible infection. On the other hand, antigen testing may not be suitable to identify loss of infectivity in COVID-19 subjects during follow-up. Newly introduced antigen tests need to be validated in a clinical or primary care setting to define their clinical usefulness.